Black phosphorus-based CuS nanoplatform: Near-infrared-responsive and reactive oxygen species-generating agent against environmental bacterial pathogens. Issue 5 (October 2022) - Naskar, Atanu; Cho, Hyejin; Kim, Kwang-sun
Abstract: Over the last few years, the two-dimensional (2D) material black phosphorus (BP) has been highlighted for its potential in various biomedical applications, owing to its excellent physical and chemical properties. Nevertheless, the synergistic photothermal–antibacterial effects of BP when combined with other semiconducting materials against pathogenic bacteria have rarely been explored. In this study, the synergistic photothermal–antibacterial activity of a BP-based CuS (CB) nanoplatform against environmental bacterial pathogens was evaluated. A low-temperature solution synthesis method was utilized to prepare CuS nanoparticles that were immobilized onto BP nanosheets. The resulting CB nanocomposite was characterized using X-ray diffraction, transmission electron microscopy, and X-ray photoelectron spectroscopy. The antibacterial activity of the samples was evaluated by determining their minimum inhibitory concentration and bactericidal activity following near-infrared irradiation. The results revealed that CB nanocomposites showed higher antibacterial activity than other samples owing to the high photothermal conversion efficiency. In addition, the plausible antibacterial mechanisms, such as the formation of reactive oxygen species and bacterial membrane disruption, were evaluated. The prepared 2D semiconductor exhibiting synergistic photothermal–antibacterial activity will serve as a good nanoplatform against multidrug-resistant pathogens shed in the environment. Graphical Abstract: ga1 Highlights: Black phosphorus-based CuS (CB) nanocomposites were synthesized at low temperature. CuS nanoparticles were assembled on black phosphorus nanosheets. CB nanocomposite showed excellent NIR-responsive photothermal conversion efficiency. CB nanocomposite showed synergistic photothermal–antibacterial activity.